Synthesis of 5-Substituted 2-Pyrrolidinones by Coupling of Organozinc Reagents with Cyclic N-Acyliminium Ions - Zaragoza-Galicia, Ivann; Santos-Sánchez, Zaira A.; Hidalgo-Mercado, Yazmín I.; Olivo, Horacio F.; Romero-Ortega, Moisés (Synthesis, 2019)
A coupling reaction between cyclic N-acyliminium ions with organozinc reagents is described. The cyclic N-acyliminium ions, generated in situ from N-substituted-5-hydroxy-2-pyrrolidinones by treatment with boron trifluoride–diethyl ether complex or titanium tetrachloride, are trapped by the organozinc reagent, which is formed from an alkyl bromide in the presence of zinc in the same reaction medium. The N-substituted-5-allyl-2-pyrrolidinones generated using this method serve as versatile intermediates for the synthesis of azabicyclic systems with indolizidine and pyrroloazepinolizidine cores.
Keywords: N-acyliminium ions; organozinc reagents; coupling reactions; 5-allyl-2-pyrrolidinones; azabicyclic systems